Indonesia-Germany Cooperation in Vocational Education and Training - Wiriadidjaja, Astrid; Andriasanti, Lelly; Jane, Andrea (Journal of Local Government Issues, 2019)
To reduce the unemployment rate, Indonesia has focused since 2007 on the development of Vocational Education and Training (VET). VET is one of solutions that would enhance human resources quality in Indonesia, which has 262 million people. However, the number of unemployed graduates from vocational education is still high until 2019. It means there is something wrong in Indonesia?s current VET system. Meanwhile in Germany, VET is a pillar of national education which is based on a dual system. This system is successful in Germany. As one of the biggest donor countries in promoting VET, Germany tries to introduce a dual education system through bilateral relations with developing countries such as Indonesia. Indonesia seems to need to try to develop VET base on dual education system through cooperation with Germany. Thus, the research question of this article is ?why does Indonesia need to make a co-operation with Germany in developing VET based on a dual education system?? To answer the research question, this paper uses qualitative method which results in the following conclusion: Cooperation with Germany would open the opportunity for abundant human resources in Indonesia to fulfill a huge labor demand in Germany particularly and Europe in general. Moreover, the cooperation makes Indonesia gain support in developing the VET system in this country and get transfer of knowledge and technology from Germany as a developed country